2010
DOI: 10.1203/pdr.0b013e3181d22a73
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Are Targeted by Rotavirus in Experimental Biliary Atresia and Induce Neutrophil Chemotaxis by Mip2/Cxcl2

Abstract: Biliary atresia is an obstructive cholangiopathy of unknown etiology. Although the adaptive immune system has been shown to regulate the obstruction of bile ducts in a rotavirus-induced mouse model, little is known about the virus-induced inflammatory response. Here, we hypothesized that cholangiocytes secrete chemoattractants in response to rotavirus. To test this hypothesis, we infected cholangiocyte and macrophage cell lines with rhesus rotavirus type A (RRV), quantified cytokines and chemokines and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 26 publications
2
44
1
1
Order By: Relevance
“…Here, we provide evidence for an alternate possibility that hepatic DCs are cellular targets of RRV and induce proliferation and activation of CD8 + T cells and NK cells, both of which have been shown to injure infected cholangiocytes and damage the duct epithelium in vivo. These results do not exclude a potential participation of cholangiocytes in attracting lymphocytes or myeloid cells after RRV infection, but experiments to quantify this response revealed relatively low levels of cytokines and chemokines in RRV-infected cholangiocytes (25, 26). Our data also do not exclude a potential role for cholangiocytes in the promotion of T cell proliferation in vivo when aided by other cells (for example, NK cells) in response to RRV infection.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Here, we provide evidence for an alternate possibility that hepatic DCs are cellular targets of RRV and induce proliferation and activation of CD8 + T cells and NK cells, both of which have been shown to injure infected cholangiocytes and damage the duct epithelium in vivo. These results do not exclude a potential participation of cholangiocytes in attracting lymphocytes or myeloid cells after RRV infection, but experiments to quantify this response revealed relatively low levels of cytokines and chemokines in RRV-infected cholangiocytes (25, 26). Our data also do not exclude a potential role for cholangiocytes in the promotion of T cell proliferation in vivo when aided by other cells (for example, NK cells) in response to RRV infection.…”
Section: Discussionmentioning
confidence: 70%
“…DCs are uniquely fitted to sense pathogens and to orchestrate an immune response by establishing intercellular circuits among themselves and with other cells (20, 26, 27). In adult mice, cDCs are the major source of IL-15 production in response to CpG oligonucleotides but require accessory signals from pDCs for appropriate responses, perhaps mediated by CD40L (20).…”
Section: Discussionmentioning
confidence: 99%
“…3), suggesting a potential contributory role for the innate immune system in toxin-induced biliary injury as identified in the RRV BA model (19). Late accumulation of macrophages around injured intrahepatic ducts is also seen in RRV-infected mice (11), where they are thought to attract neutrophils (32). Macrophage depletion also prevented duct obstruction in the RRV model (33).…”
Section: Resultsmentioning
confidence: 99%
“…Others have suggested that in rhesus macaques, rhesus RV (RRV) escapes the intestine via a lymphatic route, with the viral nonstructural proteins (NSPs) being sequentially detected in Peyer's patches, mesenteric lymph nodes (MLNs), spleen, and liver (33). RV NSPs have been observed in mouse macrophages as well as human macrophages, dendritic cells (DCs), and B cells (34)(35)(36). These results suggest that immune cells may be permissive to RV infection and may play a role in RV persistence and extraintestinal dissemination.…”
mentioning
confidence: 99%